Mitigating the Deadly Embrace in Financial Cycles : Countercyclical Buffers and Loan-to-Value Limits - Benes, Jaromir; Laxton, Douglas; Mongardini, Joannes (Washington, D.C. : International Monetary Fund, 2016)
This paper presents a new version of MAPMOD (Mark II) to study the effectiveness of macroprudential regulations. We extend the original model by explicitly modeling the housing market. We show how household demand for housing, house prices, and bank mortgages are intertwined in what we call a deadly embrace. Without macroprudential policies, this deadly embrace naturally leads to housing boom and bust cycles, which can be very costly for the economy, as shown by the Global Financial Crisis of 2008-09.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet